Closing the Gap in Education and Technology - Perry, Guillermo (World Bank, Washington, DC, 2012)
The note looks at what it takes for countries, and firms to "learn how to learn". Education is vital, for at least two reasons. First, it has always been a critical complement to technological advance. Emerging evidence suggests that the knowledge transfer benefits of foreign direct investment (FDI), and trade liberalization, for example, are enhanced by higher stocks of human capital. Second, technological change in the twentieth century has been increasingly biased in favor of skilled workers, and appears to be the strongest force driving the increasing skilled/unskilled wage differential in industrialized countries. On reviewing Latin America's gaps in education, and technology, the central premise is that skills upgrading, technological change and interactions between the two are major factors behind total factor productivity (TFP) growth, and that TFP is a key determinant of long term growth. Skill-based technological change is being transferred faster today to LAC countries that are more open to trade, and foreign direct investment (FDI) flows, and have increased the education level of their work force. Empirical evidence suggest that technological change has been complementary with skill in Latin America in the last two decades, as in more developed countries. However, despite progress in the region, educational gaps have increased and are particularly wide at secondary levels, with few exceptions. This is linked to the way educational transition has taken place, and how resources are allocated in the education sector in Latin America: a large share of resources go to public universities, frequently of low quality, leaving little funding for secondary education. These policies have constrained tertiary education expansion, and led to large gaps in secondary education, causing inefficiency and inequity. It is argued that development of the information communications technology (ICT) sector is an essential complementary instrument to develop technological capability, further suggesting the need for an integrated approach role by government, at minimum, ensuring a consistent set of incentives, and an efficient "innovation policy".